New catalysts for oxidation reactions based on polyphosphazenes - Błaż, E.; Pielichowski, J. (Polimery, 2022)
In the current work we describe the synthesis of novel polyphosphazene-based catalysts for oxidation reactions. The catalysts were prepared by a three-step reaction procedure. First, poly(dichlorophosphazene) was synthesized by thermal polymerization of the cyclic trimer of hexachlorocyclotriphosphazene. In the second stage, the poly(dichlorophosphazene) structure was converted into 2-aminopyridine and 3-aminopyridine by a nucleophilic substitution reaction. The last stage of catalyst’s synthesis was reaction of poly(diaminopyridino)phosphazenes with cobalt acetate. IR, TG and AAS were employed for characterization of the catalysts obtained. Oxidation reactions of some alkenes were carried out using synthesized catalysts at atmospheric pressure in the presence of molecular oxygen. Epoxides and ketone were obtained as main products with very high yield and selectivity.